Extracellular Vesicles Released by Leishmania (Leishmania) amazonensis Promote Disease Progression and Induce the Production of Different Cytokines in Macrophages and B-1 Cells - Barbosa, Fernanda Marins Costa; Dupin, Talita Vieira; Toledo, Mayte dos Santos; Reis, Natasha Ferraz dos Campos; Ribeiro, Kleber; Cronemberger-Andrade, André; Rugani, Jeronimo Nunes; De Lorenzo, Beatriz Helena Pizarro; Novaes e Brito, Ronni Rômulo; Soares, Rodrigo Pedro; Torrecilhas, Ana Claudia; Xander, Patricia (Frontiers in Microbiology, 2018)
The extracellular vesicles (EVs) released by Leishmania can contribute to the establishment of infection and host immunomodulation. In this study, we characterized the shedding of EVs from Leishmania (Leishmania) amazonensis promastigotes. This species is the causative agent of cutaneous leishmaniasis, and its role during interactions with bone marrow-derived macrophages (BMDMs) and peritoneal B-1 cells was evaluated. Leishmania amazonensis promastigotes cultivated in vitro at different times and temperatures spontaneously released EVs. EVs were purified using size-exclusion chromatography (SEC) and quantitated by nanoparticle tracking analysis (NTA). NTA revealed that the average size of the EVs was approximately 180 nm, with concentrations ranging from 1.8×108-2.4×109 vesicles/mL. In addition, the presence of LPG and GP63 were detected in EVs obtained at different temperatures. Naïve BMDMs stimulated with EVs exhibited increased IL-10 and IL-6 expression. However, incubating B-1 cells with parasite EVs did not stimulate IL-10 expression but led to an increase in the expression of IL-6 and TNFα. After 7 weeks post-infection, animals infected with L. amazonensis promastigotes in the presence of parasite EVs had significant higher parasite load and a polarization to Th2 response, as compared to the group infected with the parasite alone. This work demonstrated that EVs isolated from L. amazonensis promastigotes were able to stimulate macrophages and B-1 cells to express different types of cytokines. Moreover, the immunomodulatory properties of EVs probably contributed to an increase in parasite burden in mice. These findings suggest that the functionality of L. amazonensis EVs on immune system favor of parasite survival and disease progression.